Effects of counseling on the career choices of seniors of Quezon Provincial High School - Batanes, Lydia Remo 1940-
The primary purpose of this study was to determine the effects of counseling on the career decision-making of seniors of Quezon Provincial high school in Lucena City during the school year 1980-1981. The study was founded on the assumption that vocational counseling can help students arrive at a wise career choice. It made use of the pretest-posttest control group design.